Flower lose, a cell fitness marker, predicts COVID‐19 prognosis. Issue 11 (18th October 2021) - Yekelchyk, Michail; Madan, Esha; Wilhelm, Jochen; Short, Kirsty R; Palma, António M; Liao, Linbu; Camacho, Denise; Nkadori, Everlyne; Winters, Michael T; Rice, Emily S; Rolim, Inês; Cruz‐Duarte, Raquel; et al.
Abstract: Risk stratification of COVID‐19 patients is essential for pandemic management. Changes in the cell fitness marker, hFwe‐Lose, can precede the host immune response to infection, potentially making such a biomarker an earlier triage tool. Here, we evaluate whether hFwe‐Lose gene expression can outperform conventional methods in predicting outcomes (e.g., death and hospitalization) in COVID‐19 patients. We performed a post‐mortem examination of infected lung tissue in deceased COVID‐19 patients to determine hFwe‐Lose' s biological role in acute lung injury. We then performed an observational study ( n = 283) to evaluate whether hFwe‐Lose expression (in nasopharyngeal samples) could accurately predict hospitalization or death in COVID‐19 patients. In COVID‐19 patients with acute lung injury, hFwe‐Lose is highly expressed in the lower respiratory tract and is co‐localized to areas of cell death. In patients presenting in the early phase of COVID‐19 illness, hFwe‐Lose expression accurately predicts subsequent hospitalization or death with positive predictive values of 87.8–100% and a negative predictive value of 64.1–93.2%. hFwe‐Lose outperforms conventional inflammatory biomarkers and patient age and comorbidities, with an area under the receiver operating characteristic curve (AUROC) 0.93–0.97 in predicting hospitalization/death. Specifically, this is significantly higher than the prognostic value of combining biomarkers (serum ferritin, D‐dimer, C‐reactive protein, and neutrophil–lymphocyte ratio), patient age and comorbidities (AUROC of 0.67–0.92). The cell fitness marker, hFwe‐Lose, accurately predicts outcomes in COVID‐19 patients. This finding demonstrates how tissue fitness pathways dictate the response to infection and disease and their utility in managing the current COVID‐19 pandemic. SYNOPSIS: A post‐mortem examination of COVID‐19 infected lung tissues and an observational study were performed in order to evaluate whether expression of cell fitness marker hFwe‐Lose in patient's nasopharyngeal swabs could predict hospitalization or death from COVID‐19. In COVID‐19 patients with acute lung injury, hFwe‐Lose was highly expressed in the lower respiratory tract and was co‐localised with areas of cell death. The hFwe‐Lose expression in patient's nasal swabs accurately predicted subsequent hospitalization or death due to COVID‐19 infection with positive predictive values (PPVs) of 87.8–100% and negative predictive values (NPVs) of 64.1–93.2%. hFwe‐Lose outperformed conventional inflammatory biomarkers and patient age and comorbidities, with an area under the receiver operating characteristic curve (AUROC) 0.93–0.97 in predicting hospitalization/death due to COVID‐19 infection. Abstract : A post‐mortem examination of COVID‐19 infected lung tissues and an observational study were performed in order to evaluate whether expression of cell fitness marker hFwe‐Lose in patient's nasopharyngeal swabs could predict hospitalization or death from COVID‐19.